2013
DOI: 10.1161/circoutcomes.113.000089
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Emergency Medical Services Use and Its Association With Timely Stroke Treatment

Abstract: Background-Prior studies found that only about half of stroke patients arrived at hospitals via emergency medical services (EMSs), yet since then, there have been efforts to increase public awareness that time is brain. Using contemporary Get With the Guidelines-Stroke data, we assessed nationwide EMS use by stroke patients. Methods and Results-We analyzed data from 204 591 patients with ischemic and hemorrhagic stroke admitted to 1563 GetWith the Guidelines-Stroke participating hospitals with data on National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
159
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(181 citation statements)
references
References 37 publications
15
159
5
2
Order By: Relevance
“…12,13 However, we found that patients with a history of stroke were less likely to use EMS, which was inconsistent with previous reports showing no association between previous stroke and EMS utilization. 12 It was worth noting that the most powerful factor associated with increased EMS utilization was previous use of EMS. Patients with experience in using EMS may have greater awareness of the importance of appropriate use of EMS for acute stroke symptoms, and they may also have better knowledge about how to use it.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, we found that patients with a history of stroke were less likely to use EMS, which was inconsistent with previous reports showing no association between previous stroke and EMS utilization. 12 It was worth noting that the most powerful factor associated with increased EMS utilization was previous use of EMS. Patients with experience in using EMS may have greater awareness of the importance of appropriate use of EMS for acute stroke symptoms, and they may also have better knowledge about how to use it.…”
Section: Discussionmentioning
confidence: 99%
“…Arrival by emergency medical services was associated with improved DAT and DIT, 7,8 and patient factors such as blood pressure, blood glucose, National Institutes of Health Stroke Scale score of >2, intubation/high oxygen requirement, and sex were found to be significant factors that predicted activation and imaging times. [8][9][10] Interestingly, time cycle factors were significant in our study, contrasting previous research showing no association between DIT and time of day or day of week.…”
Section: Strokementioning
confidence: 94%
“…5,6 Mode of patient arrival (emergency medical services versus private vehicle) is another care process known to affect DIT. 7,8 In addition, patient-specific factors, including sex, symptom severity, symptom duration, history of diabetes mellitus, and initial blood pressure, also are reported to affect DIT. [8][9][10] Although research related to DIT in stroke is extensive, it has focused primarily on process-specific and patient-specific factors.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, the extent to which hospitals are using these strategies has not been well studied. More importantly, it is not clear which strategies are most effective.…”
Section: May 2014mentioning
confidence: 99%